Identification of scuttle fly Dohrniphora cornuta (Bigot, 1857)(Diptera: Phoridae), from edible mushroom farms in central of Iraq. - Mustafa Jewad Al-Fayyadh (University of Thi-Qar Journal of agricultural research, 2023)
The Phoridae family, which contains approximately 4,000 species in more than 260 genera, is one of the largest families of Diptera ,The scuttle fly have been found in variety of environment, they are associated with late stages of composition . In current study both males and females of Dohrniphora cornuta were collected and identified for the first time from the farms of edible mushrooms in Al-Dwaniya province, central of Iraq.The specimens were studied and identified in laboratories of Sumer university, college of soil and water sources, deposited in 70% ethyl alcohol.